Applicability of ketone-gasoline blended fuels for spark ignition engine through energy-exergy analyses. (1st May 2023) - Patil, Vishal; Singh, Paramvir; Sonage, Sachin; Kumbhakarna, Neeraj; Kumar, Sudarshan
Highlights: Applicability of ketones were investigated as potential blending fuels in commercially available premium gasoline. 2-Butanone, 4-methyl-2-pentanone, cyclopentanone and cyclohexanone were selected for investigation based on their properties. Blends were formulated with partial addition of ketones (10%, 20% and 30% by volume) in gasoline. Energy and exergy analysis, entropy generation and sustainability index of ketone-gasoline blends assessed and compared with gasoline. 10% blended ketones fuels have comparable energy-exergy and sustainability assessment as premium gasoline. 2-Butanone (30 %)-gasoline (70 %) blend has 21 % lower carbon monoxide and nitrogen oxide emissions compared to commercial gasoline at 2500 rpm engine speed. Abstract: A range of ketone biofuels was investigated as potential blending fuels with gasoline in a spark-ignition engine. The present study aims at investigating the applicability of ketone-based blended fuels with commercially available premium gasoline (RON 95) such as 2-butanone, 4-Methyl-2-pentanone, cyclopentanone, and cyclohexanone in RON95 gasoline as a potential future fuel option. The blends were formulated with the partial addition (10 %, 20 %, and 30 % by volume) of ketones in gasoline and tested with variable engine speed conditions (1500, 2500, and 3500 rpm) in a spark ignition (SI) engine. Energy-exergy analyses and sustainability assessments of ketone-gasoline blends are compared with gasoline. The higher brake thermal efficiency and exergy efficiency were found at 2500 rpm engine operating conditions than other engine speed conditions for tested fuels. The 10 % blended ketones fuels have comparable energy-exergy and sustainability assessment to that of commercial gasoline. However, 30 % ketone fuel with 70 % gasoline is more promising in terms of lower emissions than pure gasoline fuel. Among all the tested blends, BUB30 fuel has 21 % lower CO and NOx emissions as compared to commercial gasoline at 2500 rpm engine condition. The scientific impact of this research work is the applicability of selective ketone biofuels in SI engines for minimizing the hazardous emissions currently being emanated from these engines. The cost-effectiveness of ketone biofuels will help reduce the dependency on fossil fuels.